Performance of an IEEE 802.16 Wireless Backhaul in the Presence of a Node Failure - Chai, Pey San Nancy; Chung, Kah-Seng; Chan, King-Sun (IEEE (Catalog Number: CFP10806-CDR), 2010)
A wireless backhaul network is used to interconnect intermediate nodes to gateway nodes. As it is designed to serve a large population of broadband users, failure sustainability becomes an essential requirement to ensure uninterrupted telecommunication services even in the presence of occasional node or link failures. In this paper, the performance of a failure sustainable wireless backhaul, based on IEEE 802.16 radio technology, is analysed in the presence of a node failure. Furthermore, it is shown that the network performance is significantly improved by incorporating two proposed modifications, namely request-resend and dynamic mini-slot allocation, in IEEE 802.16 standard coordinated distributed scheduling.